Mitochondrial base editing: from principle, optimization to application - Jinling Tang; Kunzhao Du (Cell & Bioscience)
Abstract In recent years, mitochondrial DNA (mtDNA) base editing systems have emerged as bioengineering tools. DddA-derived cytosine base editors (DdCBEs) have been developed to specifically induce C-to-T conversion in mtDNA by the fusion of sequence-programmable transcription activator-like effector nucleases (TALENs) or zinc-finger nucleases (ZFNs), and split deaminase derived from interbacterial toxins. Similar to DdCBEs, mtDNA adenine base editors have been developed with the ability to introduce targeted A-to-G conversions into human mtDNA. In this review, we summarize the principles of mtDNA base-editing systems and elaborate on the evolution of different platforms of mtDNA base editors, including their deaminase replacement, engineering of DddAtox variants, structure optimization and editing outcomes. Finally, we highlight their applications in animal models and human embroys and discuss the future developmental direction and challenges of mtDNA base editors.